The Influence of Instagram Creative Exploration and Marketing Mix on Increasing Private Lesson Bookings: A Study Case in Ruangbelajarr.help - Ni Kadek Sintya Cahyani; Muhamad Arya Adhiwijna; Ngakan Putu Teja Kamertajaya (Eduvest - Journal of Universal Studies, 2026)
Lack of creativity in marketing using Instagram and optimizing marketing mix elements on Ruangbelajarr.help are problems that must be resolved by Ruangbelajarr.help. Based on the data that has been summarized, it shows that the utilization of Instagram social media and marketing mix activities at Ruangbelajarr.help is not optimal. The aim of the research is to describe the application and benefits of creative exploration of Instagram social media with available features such as photo and video content, live, stories, and so on. Then there are the benefits of implementing the marketing mix optimally, such as product, price, place and promotion. This research used descriptive quantitative research methods with multiple linear regression equations. The data collection techniques used were observation, questionnaires and literature study. The steps in this research are problem formulation, hypothesis formulation, data collection, validity and reliability testing, data processing, and drawing conclusions. The results of the research obtained using the T test and F test show that the influence of Instagram Creative Exploration and Marketing Mix has a significant impact on increasing private tutoring orders. The results of the multiple linear regression analysis are positive with a constant value of 15,435. In the coefficient of determination test, the data obtained was 71.7% which could be explained by the influence of Instagram Creative Exploration and Marketing Mix Component while the remaining 28,3% could be explained by other variables not researched by the author.